Importance of Business Newspapers Among Management Students: A Case Study of Rajasthan (India) - Bhandari, Deepak; Singh, Col. Bharat (PYC Nepal Journal of Management, 2010)
Newspapers have become an inseparable part of life. The present era is that of Information, which is available at the ‘Right Time to the Right Person.’ In the context of management students, it is essential that the present day newspapers are able to satisfy the academic needs in terms of content and coverage. Further the students may also look for aspects and information associated with research duly encompassing related problem areas so that in the long run, they may be able to benefit suitably in so far as the specifics of course content and professional knowledge is concerned. In the backdrop of the above mentioned facets, the main objective of the research was to study the usefulness of Business Newspapers in the course and career of management students, and to determine the respondent’s behaviour and choice criteria regarding business newspapers and finally the content preference.